Pola Pengasuhan Anak Pada Keluarga Petani Melayu Di Desa Pusaka Kecamatan Tebas Kabupaten Sambas - Purnasari, Purnasari (UNIVERSITAS TANJUNGPURA, 2013)
The Child Caring In Malay Farmers Family At Pusaka Village Sub Tebas Sambas district. Work as farmers occupied by the parents are nearly 9 hours in the fields and have 2-6 children within it self. The research aims is to analyze and determine the child caring Â applied by Malay farmers family.Â Data collection instruments are interviews, observation, and documentation.Â The results show two kinds child caring was applied In Malay Farmers Family At Pusaka Village that is democratic and authoritarian. In democratic family, problem solved with the rebuke, explaining and consequences, thus produced a confident teenager, feel welcome in society, cooperate, friendly, always wanted to know. While the authoritarian family, problem solving colored with scold parents even hitting and never give congratulations and gifts if children perform so as to produce a timid teenager, shy, insecure and easily offended.Key Words: Child Caring, Malay farmers Family, Children's Education.